Top‐Down Control of Ammonia Oxidizers by Grazing in the North Pacific - Silin Ni; Min Nina Xu; Moge Du; Edward A. Laws; Shuh‐Ji Kao (Geophysical Research Letters, 2024)
Abstract The impact of grazing pressure on ammonia oxidizers (AO) has never been quantified in the field. Here we develop a new method to quantify the grazing rates on AO in aquatic systems. We introduce 15NH4+ tracer into the traditional dilution experiments to measure AO's apparent growth rates by using the end‐product of 15NH4+ oxidation, that is, 15NOx−. Field studies in the North Pacific revealed that 15NOx− in the end‐product was sensitive enough to detect AO's grazing rates. Experiments from the lower euphotic zone showed NH4+ replete growth rates of 0.40 d−1 and 0.77 d−1 of AO and in situ grazing rates on AO of 0.41 d−1 and 0.45 d−1, respectively, indicating a strong top‐down control by grazing on AO. Compiled data show a vertical decoupling between ammonia oxidation rates and AO abundance within the euphotic zone, indicating that strong grazing may have affected the distribution of AO in the global ocean.